Exploring the Relationship Between Mobile Phone and Document Use During Business Travel - O'Hara, Kenton; Perry, Mark; Sellen, Abigail; Brown, Barry A. T. (Not stated, 2001)
Many IT companies recognise the importance of wireless communication in the development of new technologies. In order to better inform this development, this paper describes a study of mobile professionals focussing on their communication and document activities. The findings indicate the particular importance of verbal communication for these people and hence the value of the mobile phone. The study also brings to the fore the relationship between their use of the phone and their document activities. The findings have allowed us to develop a taxonomy of this relationship that provides a useful resource for thinking about design implications and new technology supporting mobile work.